Abatacept: from a budget impact model to cost-effectiveness analysis – data from RCT and real life - Benucci M; Damiani A; Manfredi M; Infantino M; Grossi V; Li Gobbi F (Dove Medical Press, 2019)
Maurizio Benucci,1 Arianna Damiani,1 Mariangela Manfredi,2 Maria Infantino,2 Valentina Grossi,2 Francesca Li Gobbi11Rheumatology Unit, S.Giovanni di Dio Hospital, Florence, Italy; 2Immunology and Allergology Laboratory Unit, S.Giovanni di Dio Hospital, Azienda USL-Toscana Centro, Florence, ItalyAbstract: Rheumatoid arthritis (RA) is a chronic inflammatory disorder that affects joints with swelling and progressive joint destruction. The pathology leads to a progressive disability with an impact on the quality of life of the patients. Strategies to reduce in-patient care costs could have a considerable impact on lowering the direct medical costs of RA in Italy. Abatacept, a selective T-cell costimulation modulator, is a valuable treatment option for patients with moderate-to-severe RA. A search using the keywords “cost-effectiveness analysis", "budget impact model", "abatacept", and "rheumatoid arthritis” was carried out on PubMed. Abatacept in the first- and second-treatment lines has been evaluated in our research. We evaluated patients with inadequate MTX response, inadequate anti-TNF agents response, switch studies and real-world data. Furthermore, in our research, we evaluated the main head-to-head studies published.Keywords: abatacept, budget impact model, cost-effectiveness analysis, rheumatoid arthritis